(3EYQGH GdbQBfs - (3RcQjG Hf eMeO Hf CMeO Hf RcQjG GdCfUGQj GdSfjcj GdeUQj GdTGaYqj, CHh jMji , J (B926 (3g` s
(3ChdgG (B:s
(3de jQhi GdGda gfG s
(3BNQgG (B:s
(3hdG GYHO eG JYHOhf s
(3HgG fXGe GdJYbjHIs
(3UaMGJgG eQbegs
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B46 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B182 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B374s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs